The pleiotropic functions of GOLDEN2-LIKE transcription factors in plants - Zheng, Mengyi; Wang, Xinyu; Luo, Jie; Ma, Bojun; Li, Dayong; Chen, Xifeng (Frontiers in Plant Science, 2024)
The regulation of gene expression is crucial for biological plant growth and development, with transcription factors (TFs) serving as key switches in this regulatory mechanism. GOLDEN2-LIKE (GLK) TFs are a class of functionally partially redundant nuclear TFs belonging to the GARP superfamily of MYB TFs that play a key role in regulating genes related to photosynthesis and chloroplast biogenesis. Here, we summarized the current knowledge of the pleiotropic roles of GLKs in plants. In addition to their primary functions of controlingcontrolling chloroplast's biogenesis and function maintainmaintenance, GLKs have been proven to regulate the photomorphogenesis of seedlingseedlings, metabolite synthesis, flowering time, leaf senescence, and response to biotic and abiotic stress, ultimately contributing into crop yield enhancement. This review will provide a comprehensive understanding of the biological functions of GLKs and serve as a reference for future theoretical and applied studies of GLKs.